Upaya Orang Tua dalam Menanamkan Amalan Ibadah Shalat pada Anak - Akhmad Asyari; Rahma Sarita Ahmad; Muhamad Ahyar Rasidi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study focuses on the efforts of parents in instilling the practice of prayer in children and what factors are the support and obstacles for parents in instilling the practice of prayer in children. This study uses a qualitative approach where the subjects in this study are community leaders, parents and children. Collecting data in this study using the methods of observation, interviews and documentation. The results showed: 1) the efforts of parents in instilling the practice of praying in children were carried out by giving advice to children, giving examples, giving special attention, training children or getting children to pray from a young age and giving punishment to children. 2) The supporting factor is the encouragement from parents, family, and adequate infrastructure in the house, while the inhibiting factor is parents who are busy with work, friendships, facilities and infrastructure in the environment that do not exist, thus hampering education for children.